Application of Mitomycin C after dilation of an anastomotic stricture in a newborn with necrotizing enterocolitis - Jonathan Green; Christopher Schlieve; Michael P. Hirsh; Pradeep Nazarey; Jeremy T. Aidlen (Elsevier, 2016)
Necrotizing enterocolitis (NEC) is a common life-threatening condition in premature infants. Bacterial translocation, localized inflammation and subsequent perforation often require surgery for source control and definitive treatment. Small and large intestinal strictures may result from either creation of a surgical anastomosis or the disease process itself. Current methods to treat strictures include, balloon dilation and surgical resection with or without anastomosis. We report the diagnosis and surgical management of a premature infant treated for NEC, who developed an anastomotic stricture and was successfully treated with topical Mitomycin C after balloon stricturoplasty.